2017
DOI: 10.3991/ijet.v12i12.7958
|View full text |Cite
|
Sign up to set email alerts
|

Design Flow of English Learning System Based on Item Response Theory

Abstract: Abstract-The popularity of computer technology in English teaching has led to the establishment of many English learning platforms, but the enhancement of students' English proficiency is limited due to the lack of relevance, self-adaptive test questions and analytical ability. The project management theory is introduced into English learning, which can provide students with teaching content and test questions that are more suitable for their own actual situation through a more intelligent, personalized way. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Zhang and VanLehn (2017) found that CAT contributed positively to students' learning outcomes. Liu and Zhao (2017) designed an English vocabulary learning system based on IRT and at the end of his experimental study, they found that the CAT was more successful by working with fewer words.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang and VanLehn (2017) found that CAT contributed positively to students' learning outcomes. Liu and Zhao (2017) designed an English vocabulary learning system based on IRT and at the end of his experimental study, they found that the CAT was more successful by working with fewer words.…”
Section: Resultsmentioning
confidence: 99%
“…Another related research was conducted by Liu [20] entitled " Design Flow of English Learning System Based on Item Response Theory". The result of this research is an English learning system based on the IRT which enables the system to provide personalized services for students and teachers.…”
Section: Previous Researchesmentioning
confidence: 99%
“…Modern test theory that is commonly known as Item Response Theory (IRT) is developed by measurement experts to minimize the the weaknesses of classical theory. Looking at the number of parameters, there are some models known as IRT, which are one-parameter logistic model, two-parameters logistic model, and threeparameters logistic model [18]. The main parameter in IRT calculation is the ability of the test takers.…”
Section: Item Response Theory (Irt) Modelmentioning
confidence: 99%